Fiscal Decentralization, Government Performance on Regional Government Financial Reporting Accountability - Sema Millenium Dua Ribu; Nurdiono Nurdiono; Reni Oktavia (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to test the effect of Fiscal Decentralization and Government Performance on Regional Government Financial Reporting Accountability. This research is a literature review research. The literature review used is the latest journal that is no more than 10 years old. The research results show that Fiscal Decentralization and Government Performance have a positive and significant effect on the Accountability of Regional Government Financial Reporting.